Chemical Conversion of Aspartic Acid 52, a Catalytic Residue in Hen Egg-White Lysozyme, to Homoserine - Eshdat, Yuval (1974)
Hen egg-white lysozyme (EC 3.2.1.17) was specifically esterified at aspartic acid 52 by the affinity labeling reagent 2′,3′-epoxypropyl β-glycoside of di-(N-acetyl-D-glucosamine) [Eshdat et al. (1973) J. Biol. Chem.248, 5892]. The disulfide bonds of the affinity-labeled enzyme and the aspartic acid 52-ester bond were reduced with dithiothreitol and sodium borohydride, respectively, resulting in the removal of the affinity label. The reduced protein contained 0.9 mole of homoserine and 1 mole less of aspartic acid per mole of protein, as compared to the native enzyme. It was reoxidized by a mixture of reduced and oxidized glutathione to yield a modified protein that possessed one-tenth of the activity of native lysozyme (presumably due to a contamination by regenerated lysozyme formed as a result of hydrolysis of the aspartic acid 52-ester bond during the chemical treatment). The native enzyme, after reduction and reoxidation in the same manner, retained its amino-acid composition, full enzymatic activity, and fluorescence properties. The modified lysozyme, containing homoserine 52, showed the same fluorescence spectrum as the native enzyme. With both proteins, the fluorescence maximum shifted to the blue to a similar extent upon the addition of the saccharide inhibitors tri-(N-acetyl-D-glucosamine) and the cell-wall tetrasaccharide (GlcNAc-MurNAc)(2). The modified enzyme bound these two saccharides with nearly the same binding constants as those found for native lysozyme and for lysozyme that was reduced and reoxidized. Since the side chain of homoserine is similar in size to that of aspartic acid, it is concluded that the loss of enzymatic activity is the direct result of the chemical modification of the carboxyl side chain of aspartic acid 52, thus showing that this amino acid is essential for the catalytic action of the enzyme.